Social Networking Addiction and Quality of Academic Life among First-Year High School Students in Saudi Arabia: The Mediating Role of Academic Procrastination - Khalifa, Ayman Gamal (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Students with high levels of procrastination were unable to organize and achieve their academic goals. A student who procrastinates may face internal consequences such as low academic performance, bad learning habits, and low learning motivation. When he/she is unable to address procrastination, this will hinder his/her academic performance. The study group of the research consists of 258 boys studying in high schools in the Riyadh region in the 2019-2020 academic year. They aged 16-18 years, (M= 17.23,SD= 4.45). Social Media Addiction Scale - Student Form, High-School Satisfaction Scale, and Tuckman’s procrastination scale –short form were used for gathering and analyzing data. Quality of academic life correlates negatively with social networking addiction and academic procrastination. On the other hand, social networking addiction was found to be positively correlated with academic procrastination. Regression coefficients of the empirical model show that social networking addiction had a direct negative effect on the quality of academic life (b= -0.49, p<0.001) and a direct positive effect on academic procrastination (b=0.52, p<0.001). Results support previous research showing that social networking addiction negatively impacts academic achievement by creating academic procrastination, reducing sleep quality, and increasing academic stress. Evidence indicates a positive and significant correlation between inappropriate and problematic use of technology and quality of academic life. Procrastination may interrupt the academic performance, as procrastinators are likely to avoid completing the task at Hand until the last moment. They may also be unable to invest the time and effort necessary for performing as they underestimate the amount of time required for completing specific tasks.